Effect of nano-silicon on the regulation of ascorbate-glutathione contents, antioxidant defense system and growth of copper stressed wheat (Triticum aestivum L.) seedlings - Riaz, Muhammad; Zhao, Shaopeng; Kamran, Muhammad; Ur Rehman, Naveed; Mora-Poblete, Freddy; Maldonado, Carlos; Hamzah Saleem, Muhammad; Parveen, Aasma; Ahmed Al-Ghamdi, Abdullah; Al-Hemaid, Fahad M.; Ali, Shafaqat; Elshikh, Mohamed S. (Frontiers in Plant Science, 2022)
Copper (Cu2+) toxicity can inhibit plant growth and development. It has been shown that silicon (Si) can relieve Cu2+ stress. However, it is unclear how Si-nanoparticles (SiNPs) relieve Cu2+ stress in wheat seedlings. Therefore, the current study was conducted by setting up four treatments: CK, SiNP: (2.5 mM), Cu2+: (500 µM), and SiNP+Cu2+: (2.5 mM SiNP+500 µM Cu2+) to explore whether SiNPs can alleviate Cu2+ toxicity in wheat seedlings. The results showed that Cu2+ stress hampered root and shoot growth and accumulated high Cu2+ concentrations in roots (45.35 mg/kg) and shoots (25.70 mg/kg) of wheat as compared to control treatment. Moreover, Cu2+ treatment inhibited photosynthetic traits and chlorophyll contents as well as disturbed the antioxidant defense system by accumulating malondialdehyde (MDA) and hydrogen peroxidase (H2O2) contents. However, SiNPs treatment increased root length and shoot height by 15.1% and 22%, respectively, under Cu2+ toxicity. Moreover, SiNPs application decreased MDA and H2O2 contents by 31.25% and 19.25%, respectively. SiNPs increased non-enzymatic compounds such as ascorbic acid-glutathione (AsA-GSH) and enhanced superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbic peroxidase (APX) activities by 77.5%, 141.7%, 68%, and 80%, respectively. Furthermore, SiNPs decreased Cu2+ concentrations in shoots by 26.2%, as compared to Cu2+ treatment alone. The results concluded that SiNPs could alleviate Cu2+ stress in wheat seedlings. The present investigation may help to increase wheat production in Cu2+ contaminated soils.